Allograft lateral collateral ligament reconstruction for bilateral chronic varus instability of the hallux interphalangeal joint: A case report and literature review. Issue 5 (July 2021) - Kim, Jaeyoung
Highlights: Chronic varus instability of the hallux interphalangeal joint is a rare condition. Reconstruction of the lateral collateral ligament using autograft tendon harvest has been linked to donor site morbidity. Allograft lateral collateral ligament reconstruction can be a viable option to avoid donor site morbidity. Abstract: The hallux interphalangeal joint (HIPJ) is anatomically stable in the transverse plane. Therefore, chronic varus instability of this joint is an extremely rare condition. For symptomatic patients, surgical reconstruction of the lateral collateral ligament is a mobility-sparing option. To date, only lateral collateral ligament reconstruction using autograft tendon has been reported. We present a case of bilateral chronic varus instability of HIPJ in a Taekwondo player, who underwent lateral collateral ligament reconstruction using Achilles tendon allograft.